2012
DOI: 10.1002/ejlt.201100347
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of supercritical fluid extraction of linseed oil using RSM

Abstract: The objective of the present study was to develop a supercritical fluid extraction (SFE) method, suitable for extraction of total oil content from linseed, and to be used as a preparative technique for fatty acid determination. Optimum conditions (volume of added ethanol as a co-solvent, dynamic extraction time (DET), and pressure) were predicted in order to obtain the maximum yield of the extract. Response surface methodology (RSM) and central composite rotatable design (CCRD) were used for modeling the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…In this work we have compared our proposed SFE-ELSD method with the AOAC Method 945.16, a modification of the AOCS Method Ba 3-38, both based on Soxhlet extraction. On a more general note, this is the method that is usually seen as the reference method of choice in the literature when proposing new methods for total lipid determination, for example [8,[22][23]. The other suggested reference method is based on solvent extraction using a Butt-type apparatus, much like the Soxhlet apparatus.…”
Section: Methods Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work we have compared our proposed SFE-ELSD method with the AOAC Method 945.16, a modification of the AOCS Method Ba 3-38, both based on Soxhlet extraction. On a more general note, this is the method that is usually seen as the reference method of choice in the literature when proposing new methods for total lipid determination, for example [8,[22][23]. The other suggested reference method is based on solvent extraction using a Butt-type apparatus, much like the Soxhlet apparatus.…”
Section: Methods Validationmentioning
confidence: 99%
“…Ivanov and Čolović [8] optimized the operating conditions for extraction of lipids from linseed using SFE. The conclusions were that a minor addition of ethanol mixed with the sample and the highest possible pressure of 62 MPa generated the highest recovery of lipids.…”
Section: Abrahamsson Et Al / Analytica Chimica Acta 853 (2015) 32mentioning
confidence: 99%
“…A LECO TFE2000 fat analyzer (Michigan, USA) was used for SFE, using CO 2 with 99.995% purity. Extraction conditions were adjusted as explained in the paper by Ivanov et al (2012). FA methyl esters were prepared from the extracted lipids by transmethylation that uses 14% (w/w) boron trifluoride/methanol solution (Karlović and Andrić, 1996;Ivanov et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Extraction conditions were adjusted as explained in the paper by Ivanov et al (2012). FA methyl esters were prepared from the extracted lipids by transmethylation that uses 14% (w/w) boron trifluoride/methanol solution (Karlović and Andrić, 1996;Ivanov et al, 2012). The obtained samples were analysed by gas chromatography on an Agilent 7890A system (Agilent Technologies; Santa Clara, CA, USA) with a flame ionization detector (GC-FID), autoinjection module for liquid, equipped with fused silica capillary column (Supelco SP-2560 Capillary GC Column 100 m × 0.25 mm, d = 0.20 μm) (Supelco; Bellefonte, USA) and helium as a carrier gas (purity = 99.9997 vol %, flow rate = 1.5 ml · min -1 and pressure = 1.092 bar).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, on linseed, SFE optimization (Bozan and Temelli, 2002;Ivanov, 2012;Jiao, 2008;Özkal, 2009;Rombaut, 2013) showed that an increase of temperature and pressure increased the oil yield. Depending on extraction conditions, up to 82% of oil could be extracted with neat CO 2 .…”
Section: Introductionmentioning
confidence: 99%